1982
DOI: 10.1016/s0006-3495(82)84684-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation of crystalline arrays of chlorophyll a/b - light-harvesting protein by membrane reconstitution

Abstract: The structure of the major protein constituent of photosynthetic membranes in higher plants, the chlorophyll a/b-light harvesting complex (LHC), was studied by x-ray diffraction and electron microscopy. The LHC was purified from Triton X-100 solubilized thylakoid membranes of the pea, and contained 6 mol of chlorophylls a and b per mole of a polypeptide of 27,000 molecular weight. X-ray diffraction showed that in the presence of 10 mM MgCl2, purified LHC forms planar aggregates that stack with a period of 51 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…It has been estimated that one LHC-I1 structural unit (see Fig. 1D) consists of 4-7 individual polypeptides of 25-29 kdaltons, each of which binds 6-13 Chl a + b in the native complex [21,44,49]. A surface-exposed segment of the LHC-I1 (amino-acid sequence shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that one LHC-I1 structural unit (see Fig. 1D) consists of 4-7 individual polypeptides of 25-29 kdaltons, each of which binds 6-13 Chl a + b in the native complex [21,44,49]. A surface-exposed segment of the LHC-I1 (amino-acid sequence shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The purified protein has been incorporated into phospholipid vesicles and induced to crystallize in the plane of the lipid bilayer (13)(14)(15)(16). Using x-ray diffraction and electron microscopy, Li and Hollingshead (16) showed that LHC lattices in the reconstituted membranes are hexagonal, with a lattice constant of 125 A and a thickness of 70 A.…”
mentioning
confidence: 99%
“…In this study, the LHC lattices have been isolated from the reconstituted membranes (16) by eliminating the contiguous pure lipid phase. The three-dimensional structure of the lattice in negative stain has been determined by image reconstruction from electron micrographs (28,30).…”
mentioning
confidence: 99%
“…Poor lipid synthesis might generate the pleiotropic phenotype of v*-424. LHC is one of few membrane proteins that self-assembles into sheets in the absence of polar glycerolipid (19) and thus might be less affected than other thylakoid complexes. We analyzed the lipid content of developing mutant thylakoids in order to ascertain whether there was any reduction of glycerolipid content that accompanied the greatly reduced levels of most thylakoid polypeptides.…”
Section: Resultsmentioning
confidence: 99%